2018
DOI: 10.1111/and.13137
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microanatomical and hormonal alterations following use of antiretroviral therapy inSprague Dawleyrats: Role of Naringenin

Abstract: Human immunodeficiency virus-infected man may require assisted reproductive technology not just for safer conception but also due to subfertility. The study investigated the effect of antiretroviral drugs on the fertility potentials of males and the possible protective role of Naringenin, using Sprague Dawley rats. Thirty adult male Sprague Dawley rats were grouped into-A: Distilled water; B: Highly Active Antiretroviral Therapy (HAART); C: Naringenin 40 mg/kg; D: Naringenin 80 mg/kg, E: HAART + Naringenin 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…However, these changes in enzyme activity had no consequences on testosterone levels. Oppositely, oral administration of naringenin (14) to male rats for 10 weeks resulted in increased serum testosterone levels [78]. Therefore, the route of delivery of flavonoids may influence the result outcome in certain experimental designs.…”
Section: Flavanonesmentioning
confidence: 99%
“…However, these changes in enzyme activity had no consequences on testosterone levels. Oppositely, oral administration of naringenin (14) to male rats for 10 weeks resulted in increased serum testosterone levels [78]. Therefore, the route of delivery of flavonoids may influence the result outcome in certain experimental designs.…”
Section: Flavanonesmentioning
confidence: 99%
“…This report suggested that both types of oil should be considered in future therapeutic approaches for controlling adverse impacts of obesity on male fertility. Adana et al assessed the beneficial effects of naringenin (40, 80 mg/kg for 10 weeks) to treat reproductive problems in highly active antiretroviral therapy (HAART) exposed SD rats [ 68 ]. Naringenin is a flavone extract from citrus species which is famous for its bioactivities related with scavenging free radicals and protecting testicular toxicity.…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…Symfi™ containing tenofovir (TDF, 300 mg), lamivudine (3TC, 300 mg) and efavirenz (EFV, 600 mg) (Elliott & Chan, 2018) was obtained from the Pharmaceutical Department of Federal Teaching Hospital, Ido‐Ekiti, Nigeria. The dosage of Symfi administered was calculated for animal from the human therapeutic dose equivalent for a rat model (Adana et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…All the treatments were conducted daily by oral administration, and after 8 weeks, the animals were killed by cervical dislocation 24 hr after the last treatment (Adana et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation